Membangun Jiwa Wirausaha Siswa Jurusan Pemasaran Sekolah Menengah Kejuruan Negeri 1 Baubau Melalui Pelatihan Pemanfaatan Pemanfaatan Pelepah Pisang Menjadi Keripik - Kuswinton; Aswira, Resfika (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2023)
The challenge of vocational education is to prepare the workforce in quantity and quality aspects specifically for the needs of various sectors, namely industrial and service sectors. In this era of globalization which is very competitive in various fields of life, it seems that vocational education is very important due to the increasing demand for human resources in the labor market. To help in the preparation Sekolah Menengah Kejuruan (SMK, or vocational high school) students after graduating the school, SMK student skills and knowledge must be improved. The aim of this community engagement is to foster the entrepreneurial spirit of the state vocational school, SMKN 1 Baubau students through training on using banana stems to make chips that can provide added value. The methods used were the first socialization discussing the processing of banana fronds, conducting training on making chips from banana fronds, assisting students in conducting training on banana fronds into chips, and empowering students of SMK Negeri 1 Baubau to shape their souls to become entrepreneurs. The result of this community engagement is to provide new knowledge to students in entrepreneurship, knowing that banana fronds can be a product. In addition, students are able to make chip products more developed in a delicious and useful way, so that they become attractive products for students. This community engagement or service also fosters the entrepreneurial spirit of students from an early age as entrepreneurs. With this banana chip product, students have been able to evolve and innovate it through different flavors. Therefore, this service can also provide training to students to use banana stems to make chips. Tantangan pendidikan kejuruan adalah untuk menyiapkan tenaga kerja baik secara kuantitas dan kualitas untuk keperluan bermacam sektor industri dan jasa. Pada jaman globalisasi yang serba kompetitif di bermacam bidang kehidupan saat ini tampaknya pendidikan kejuruan menjadi sangat penting, mengingat tuntutan sumber kekuatan manusia di pasaran tenaga kerja yang bertambah tinggi. Untuk mempersiapkan lulusan SMK yang memenuhi kualifikasi pasar kerja, maka kompetensi lulusan SMK wajib ditingkatkan. Tujuan PKM ini adalah untuk menumbuhkan jiwa wirausaha siswa SMKN 1 Baubau melalui pelatihan tentang pemanfaatan  pelepah pisang menjadi keripik yang dapat memberi nilai tambah. Metode pengabdian ini yaitu sosialisasi, membahas tentang pengolahan pelepah pisang, melakukan pelatihan pembuatan keripik dari pelepah pisang, pendampingan terhadap siswa dalam melakukan pelatihan pelepah pisang menjadi keripik, pemberdayaan siswa SMK Negeri 1 Baubau agar termotivasi menjadi wirausaha. Hasil pengabdian ini antara lain memberikan pengetahuan baru kepada siswa dalam berwirausha pelepah pisang dapat dijadikan produk. Setelah itu, siswa mampu membuat produk keripik lebih dikembangkan dengan nikmat dan bermanfaat, sehingga menjadi produk yang menarik dan menjadi peluang berwirausaha. Pengabdian ini juga memupuk jiwa wirausaha siswa sejak dini sebagai wirausaha. Adanya produk keripik pisang ini, siswa telah mampu berevolusi dan berinovasi dengan rasa yang berbeda. Oleh karena itu, pengabdian ini juga dapat memberikan pelatihan atau pengetahuan kepada siswa untuk memanfaatkan pelepah pisang menjadi keripik.